Flow dynamics in the Long Xuyen Quadrangle under the impacts of full-dyke systems and sea level rise - Tri, Van Pham Dang; Trung, Nguyen Hieu; Tuu, Nguyen Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 3, 2012)
Abstract: